O cognitivismo e não cognitivismo moral e sua influência na formação do pensamento jurídico - Ferreira Neto, Arthur Maria (2013)
Every philosophical tradition that looks at the problem concerning the criteria that defines the correct/appropriate or the incorrect/inappropriate human action assumes a notion of moral reality (even if this is represented in a fragmented way or even if it is represented as something elusive or incapable of being known by human agents), which aims to reach or represent what is captured by judgments of right and wrong. Considering the basic dimension of this type of speculation about human action, this represents the first major disagreement that arises when one intends to establish and understand the starting point that is adopted by one or other of the most relevant philosophical traditions. This being so, it is relevant to study and classify the various proposals in meta-ethics. This study therefore has the claim to first conceptualize and classify those that, today, are defined as the major theoretical proposals developed in moral philosophy, so that it may be possible the relevant influences that these different traditions engaged in the formation of some of the most prominent schools of legal thought. Two basic divisions are commonly held when analyzing the most important meta-ethical lines of thought. First we have the distinction between cognitivism and non-cognitivism, which dispute the possibility of speaking about a moral reality, i.e., an instance of reality in which judgments of right and wrong about human action can be produced and communicated with some intelligibility and objectivity. A second relevant division which represents a specification of the first allows a more specific classification of ethical traditions, so that it is common to enumerate them, from a single comparative parameter, as nihilist, emotivist, subjectivist, relativist, constructivist and realist. These meta-ethical proposals allow us to identify the elements of influence that are present in some of the most important schools of legal thought. That's because whenever one intends to answer questions that are prior to the correct understanding of legal phenomenon, one is, invariably, applying a meta-ethical scheme of thought. In this work, therefore, we shall analyse four different legal traditions, i.e., legal empiricism (usually called "legal realism"), legal positivism, the notion of law as integrity and the tradition of natural law (Natural Law Theory). Each tradition will here be represented by one author, not with the intention to explore the details and the idiosyncrasies of the particular ideas of each author, but only in order to illustrate the theoretical matrix that each adopts. Thus, the philosophers of law that will be here presented are Oliver Wendell HOLMES Jr., Hans KELSEN, Ronald DWORKIN, John FINNIS